Delamination formation and suppression during rotary ultrasonic elliptical machining of CFRP. (15th February 2020) - Geng, Daxi; Liu, Yihang; Shao, Zhenyu; Zhang, Mingliang; Jiang, Xinggang; Zhang, Deyuan
Abstract: As a superior hole manufacturing process, rotary ultrasonic elliptical machining (RUEM) has been successfully employed for drilling carbon fiber reinforced plastics (CFRPs) recently. The delamination of CFRP during drilling is generally considered as the most undesirable form of damage and the most challenging failure mode. In order to reduce the delamination in this novel process, it is important to understand the formation and suppression mechanisms during RUEM of CFRP. In this study, the delamination formation in both core drilling (CD) and RUEM was observed and analyzed. The variation trend of delamination factor with feed speed as well as cutting speed was obtained. The experimental results show that, compared with CD, RUEM method can effectively reduce hole exit delamination by 5.4%–19.3% between 1/2 plies and 0.7%–8.4% between 2/3 plies at the feed rates from 50 to 100 μm/rev. Moreover, the delamination suppression mechanism in RUEM was fully analyzed and verified. In a word, in the industry practice, RUEM can be considered as a competitive and promising technique to drill CFRP compared to other delamination suppression techniques.